Cross-Market Effects of Consolidation: Evidence from Banking - Bird, Andrew; Du, Ding; Karolyi, Stephen A (The Review of Corporate Finance Studies, 2024)
Abstract The U.S. banking sector had nearly 70% fewer banks in 2022 relative to 1989, primarily because of mergers. We develop a methodology to estimate cross-market spillover effects of bank mergers and test whether the operations of incumbents facing consolidating competitors in one market are affected in other markets. We find that nonmerging banks within a market that are one standard deviation more exposed to mergers in other markets increase deposits by 2.1% relative to their less exposed competitors. Our methodology may be applied elsewhere to assess the aggregate impacts of industry consolidation and illustrates challenges with product-based or geographic market definitions.